2017
DOI: 10.1136/bmjopen-2017-017197
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence and attitudes towards smoking among Estonian physicians: results from cross-sectional studies in 2002 and 2014

Abstract: ObjectivesTo explore smoking prevalence and attitudes towards smoking among Estonian physicians in 2002 and 2014.DesignTwo self-administered cross-sectional postal surveys were conducted among practising physicians in Estonia.ParticipantsInitial sample consisted of all practising physicians in Estonia. The corrected response rate was 67.8% in 2002 and 53.1% in 2014. Present study sample was restricted to physicians younger than 65 years (n=2549 in 2002, n=2339 in 2014).MethodsAge-standardised prevalence of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(17 reference statements)
2
4
0
Order By: Relevance
“…Previous results from a study based on Estonian physicians smoking survey showed physicians in Estonia agreeing that it is important to reduce smoking among the population. 24 Present study results complement this information by showing that physicians were ready to intervene.…”
Section: Discussionsupporting
confidence: 74%
“…Previous results from a study based on Estonian physicians smoking survey showed physicians in Estonia agreeing that it is important to reduce smoking among the population. 24 Present study results complement this information by showing that physicians were ready to intervene.…”
Section: Discussionsupporting
confidence: 74%
“…However, intention to quit has been shown to decrease with increasing age 25 . These findings might reflect a relationship between health issues and quitting smoking, since it has been shown that smoking physicians tend to believe that many people have smoked all their lives to an old age and did not become ill, hence smoking is not as dangerous as experts declare 18 .…”
Section: Associations Between Desire To Quit Smoking and Factors Relamentioning
confidence: 95%
“…The present study was based on aggregated data of cross-sectional postal smoking surveys among physicians [20, 21] and health behaviour surveys among adult population in Estonia in 2002 and 2014 [22, 23].…”
Section: Methodsmentioning
confidence: 99%
“…The methods used in two cross-sectional postal surveys among physicians have been extensively described elsewhere [20, 21]. In short, all practicing physicians who were permanent residents of Estonia were eligible for sampling in 2002 ( n = 4140) and 2014 ( n = 5666).…”
Section: Methodsmentioning
confidence: 99%